Back-extraction of major actinides from organic phase through precipitation - Réaux-Durain, Julie; Mortada, Boushra; Bertrand, Murielle; Maynadié, Jérôme; Carboni, Michaël; Meyer, Daniel; Bourgeois, Damien (Comptes Rendus. Chimie)
Recycling waste nuclear fuel through the production of mixed oxide (MOx) fuel allows for sustainable management of natural nuclear resources. With the aim of reducing the number of steps required for recycling U and Pu, the possibility of precipitating them directly from the organic phase (also referred to as precipitation stripping) using oxalic acid, is investigated herein. For practical reasons, proof-of-concept studies were performed using U(VI) and Th(IV), with the latter serving as a first model for Pu(IV). The results obtained show that, by controlling the concentrations of oxalic and nitric acids in the precipitation medium, total precipitation of Th and partial precipitation of U from the organic phase are attained. The actinides are precipitated in the form of oxalates, with the complete absence of impurities. Furthermore, the precipitates obtained can then be totally separated through washing with water, as proven by X-ray diffraction (XRD) and energy-dispersive X-ray (EDX) analyses. This allows control over the U:Th mass ratio in the final product. This work demonstrates the effectiveness of precipitation stripping using oxalic acid for the stripping of Th and U present in the organic phase, eliminating the need for reducing agents classically employed in the PUREX process.